HUBUNGAN TINGKAT KECEMASAN LANSIA DENGAN KESIAPAN PEMBERIAN VAKSINASI COVID-19 DI NAGARI AIA TAJUN KECAMATAN LUBUK ALUNG - Helman Pelani; Henniwati Henniwati; Hega Valentine (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Coronaviruses are a large family of viruses that cause disease in humans and animals. In humans, it usually causes respiratory tract infections, ranging from the common cold to serious diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Vaccination is the administration of vaccines in order to actively generate or increase a person's immunity against certain diseases, so that if one day a certain disease will not get sick or experience mild illness and will not become a source of transmission. This study aims to determine the